La cooperación entre servicios de inteligencia en el marco de la Unión Europea: ¿cooperación trasnacional o multinacional? - Díaz, Gustavo (UNISCI Discussion Papers, 2007)
Detecting and assessing the so-called “new threats” correctly requires increased intelligence cooperation between agencies from different countries. Such cooperation is also imperative for the operational implementation of the required multilateral responses to the “new” security channels. Given its toolkit, the EU offers a natural framework for intensified intelligence cooperation. Since intelligence objectives and methods are not determined by some abstract political requirement but are driven by an individual intelligence service that is trying to anticipate and satisfy the needs of its political masters, a European intelligence policy need not be a highly formalized and institutionalized affair. Such a policy would be compatible with existing loyalties and alliances. It would not only allow the persistence of special relationships, but might even revive them. It would not jeopardize specific security interests, but allow inteligence cooperation whenever possible and desirable.